Impact of Natural Ventilation on the Thermal and Energy Performance of Buildings in a Mediterranean Climate - A. Moret Rodrigues; Miguel Santos; M. Glória Gomes; Rogério Duarte (Buildings, 2019)
Natural ventilation plays an important role on the thermal and energy performance of a building. The present study aims to analyze the natural ventilation conditions of a dwelling in a Mediterranean climate and their impacts on the thermal and energy performance using an advanced building energy simulation tool. Several multi-zone simulations were carried out. In the summer, the simulations were performed under free-floating conditions, whereas in the winter they were carried out under controlled temperature conditions. In the summer, ventilation scenarios with windows opened during certain periods of time and with or without permanent openings in the facades were analyzed. The existence of permanent openings proved to be an important factor of temperature control by lowering the average indoor zone temperatures during the day. Cross-ventilation also showed to be effective. In the winter, we simulated the existence or absence of permanent openings for room ventilation and their surface area. The results showed that the stack effect plays an important role in the ventilation and that in general it outperforms the wind effect. Sizing permanent openings according to the standard guidelines proved to be adequate in providing the expected ventilation rates on an average basis.